INTERMITTENT MICRO-SEISMIC ACTIVITIES AROUND SYOWA STATION, EAST ANTARCTICA - カミヌマ, カツタダ; アカマツ, ジュンペイ; KAMINUMA, Katsutada; AKAMATSU, Junpei (National Institute of Polar Research, 1991)
P(論文) Antarctica seems to be the only one aseismic continent on the earth. No large earthquakes of which magnitude is larger than 5 have been located in the Antarctic Continent, although, small and micro-earthquake activities are detected by the worldwide seismic network and some local networks in the Antarctic. A tripartite seismic array was established at Syowa Station (69°S, 39°E) in 1987 for studying the local seismicity. Ten micro-earthquakes were recorded by the tripartite array during 19 months from June 1987 to January 1989. These earthquakes are located in the geological and geophysical structural boundaries of the coastal area in the Antarctic Continent and offshore. Other four earthquakes were recorded during 9 months from February to October, 1989. The local earthquakes around Syowa Station occurred intermittently. There are many well-developed elevated beaches and marine terraces in the coastal ice-free area of the Antarctic Continent. These have been formed by the relative lowering of sea level, caused by the crustal uplift after the deglaciation. The local micro-earthquakes seem to have been caused by the tectonic stress which was accumulated by the slow-moving crustal uplift. As local earthquakes occur intermittently, it seems that the crustal uplift is not a linear movement but an intermittent one, and the local earthquakes occur corresponding with the intermittent crustal uplift. departmental bulletin paper